2022
DOI: 10.1039/d2qm00453d
|View full text |Cite
|
Sign up to set email alerts
|

Surface defect-regulated PdCu/TiO2−x promoting efficient electrocatalytic nitrogen reduction

Abstract: Due to the utilization of renewable energy and proton sources, electrochemical nitrogen reduction reaction is considered as an efficient, sustainable, and carbon-neutral route to replace the industrial Haber-Bosch process. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…As a result, the desorption of *N 2 is inhibited and the formation of *NNH is promoted, consistent with the NRR study. 32…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the desorption of *N 2 is inhibited and the formation of *NNH is promoted, consistent with the NRR study. 32…”
Section: Resultsmentioning
confidence: 99%
“…151 Moreover, Liu et al synthesised PdCu alloys supported on O vacancy-rich TiO 2 via the co-reduction method and revealed that the realized synergistic effect originates from the introduction of Cu for alloy architecture and the defect-rich surface. 152 In particular, the pure transition metal alloy can employ for the NRR. Castellano-Varona et al alloyed Co with Mo to improve the poor NRR activity of Co NPs.…”
Section: Nrr On Metal and Alloy Nanoparticlesmentioning
confidence: 99%
“…Xue et al introduced Ni to Au nanoparticles and further boosted the NRR process with a FE of 67.8% 151. Moreover, Liu et al synthesised PdCu alloys supported on O vacancy-rich TiO 2 via the co-reduction method and revealed that the realized synergistic effect originates from the introduction of Cu for alloy architecture and the defect-rich surface 152. In particular, the pure transition metal alloy can employ for the NRR.…”
mentioning
confidence: 99%
“…The electrocatalytic nitrogen reduction reaction (NRR) is an alternative method for green and sustainable NH 3 synthesis under ambient conditions. However, the electrocatalytic conversion of the NRR suffers from a low NH 3 production rate and unsatisfactory partial current densities of NH 3 (mostly <1 mA cm –2 ), owing to the strong NN triple bond (941 kJ mol –1 ) and low solubility of N 2 in aqueous solution. From the energy and environmental viewpoints, the electrochemical nitrate reduction reaction (NO 3 RR) is considered an attractive alternative for large attainable NH 3 production due to the low dissociation energy of NO (204 kJ mol –1 ) and the high NO 3 – solubility. In addition, NO 3 – is widely abundant as groundwater pollution in industrial wastewater, liquid nuclear waste, chemical fertilizers, and livestock excrement, resulting in a threat to human health. , Therefore, the NO 3 RR is highly attractive for producing value-added NH 3 by turning waste into treasure, opening up an economical and feasible way to synthesize green NH 3 . , …”
Section: Introductionmentioning
confidence: 99%